Testing and commissioning of Malaysian grid connected PV system calculator using Visual Basic 2008 / Aizat Noor Azmi - Noor Azmi, Aizat (2010)
This thesis presents a Testing and Commissioning of Malaysian Grid Connected PV System Calculator using Visual Basic 2008. This thesis report initially will discuss the basic operation of a photovoltaic system and testing and commissioning for photovoltaic system. Besides that, this thesis also will discuss about the data that include in testing and commissioning process. Visual basic software is used in create virtual form and to create calculator which the final. exe file can be run at any computer and notebook.